Organothrips stongensis sp. n. and Watanabeothrips yasuakii Okajima: new records from Peninsular Malaysia of Thysanoptera: Thripidae - Ng, Y. F. (Zootaxa, 2017)
Organothrips stongensis sp. n. is described from Malaysia based on two males. These are sharply bicolored in contrast to other males in this genus, and a key is provided to males of the four known species of this genus. Organothrips was not previously known in Malaysia. Watanabeothrips yasuakii Okajima is also a first record from Malaysia, and differences between these females and the holotype decription are discussed.